2022
DOI: 10.3389/fpls.2021.749439
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping for Yield Attributing Traits and Yellow Mosaic Disease Resistance in Mung Bean [Vigna radiata (L.) Wilczek]

Abstract: Mung bean [Vigna radiata (L.) Wilczek] is an important short-duration grain legume widely known for its nutritional, soil ameliorative, and cropping system intensification properties. This study aims at evaluating genetic diversity among mung bean genotypes and detecting genomic regions associated with various yield attributing traits and yellow mosaic disease (YMD) resistance by association mapping. A panel of 80 cultivars and advanced breeding lines was evaluated for 10 yield-related and YMD resistance trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Successful transferability of SSRs from adzuki bean, common bean, and scarlet runner bean was Frontiers in Genetics frontiersin.org reported earlier in mungbean (Wang et al, 2009;Dikshit et al, 2012;Gupta et al, 2013a;Pratap et al, 2015;Pratap et al, 2016;Pratap et al, 2020;Kumari et al, 2021). Earlier, cross-genera-and cross-species-specific SSRs have been very well utilized in linkage and association mapping for identifying genes/QTLs responsible for various traits in mungbean, blackgram, V. marina, and cowpea in addition to their use in studying genetic diversity (Isemura et al, 2012;Gupta et al, 2013b;Singh et al, 2020;Rohilla et al, 2021;Vadivel et al, 2021). Agronomically important yield-attributing traits, namely, PH, NSP, HSW, DF, DM, and resistance to various biotic and abiotic stresses, in most of the crop plants are likely to be controlled by many genes/QTLs with additive gene actions (Bharadwaj et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Successful transferability of SSRs from adzuki bean, common bean, and scarlet runner bean was Frontiers in Genetics frontiersin.org reported earlier in mungbean (Wang et al, 2009;Dikshit et al, 2012;Gupta et al, 2013a;Pratap et al, 2015;Pratap et al, 2016;Pratap et al, 2020;Kumari et al, 2021). Earlier, cross-genera-and cross-species-specific SSRs have been very well utilized in linkage and association mapping for identifying genes/QTLs responsible for various traits in mungbean, blackgram, V. marina, and cowpea in addition to their use in studying genetic diversity (Isemura et al, 2012;Gupta et al, 2013b;Singh et al, 2020;Rohilla et al, 2021;Vadivel et al, 2021). Agronomically important yield-attributing traits, namely, PH, NSP, HSW, DF, DM, and resistance to various biotic and abiotic stresses, in most of the crop plants are likely to be controlled by many genes/QTLs with additive gene actions (Bharadwaj et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Successful transferability of SSRs from adzuki bean, common bean, and scarlet runner bean was reported earlier in mungbean ( Wang et al, 2009 ; Dikshit et al, 2012 ; Gupta et al, 2013a ; Pratap et al, 2015 ; Pratap et al, 2016 ; Pratap et al, 2020 ; Kumari et al, 2021 ). Earlier, cross-genera- and cross-species-specific SSRs have been very well utilized in linkage and association mapping for identifying genes/QTLs responsible for various traits in mungbean, blackgram, V. marina , and cowpea in addition to their use in studying genetic diversity ( Isemura et al, 2012 ; Gupta et al, 2013b ; Singh et al, 2020 ; Rohilla et al, 2021 ; Vadivel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noble et al ( 71 ) and Breria et al ( 72 ) previously reported the occurrence of four subpopulations among the 466 different mungbean accessions and 297 mungbean minicore collections, respectively. Versha et al ( 73 ) recently discovered four subpopulations in an association mapping analysis comprising 80 genotypes. The genomic resources developed in this study will pave the way for the discovery of SNPs/candidate genes linked to agronomic traits in mungbean.…”
Section: Discussionmentioning
confidence: 99%
“…It is an autogamous crop with 2n = 2x = 22 chromosomes that span about 574 Mega base pairs of genetic material [4]. The small genome size makes it a suitable model crop for studying evolutionary and genetic diversity [5].…”
Section: Introductionmentioning
confidence: 99%